The Pursuit of the Source, or The Inevitability of Death - Persson, Mats; Karlsson, Jan Ch. (Nordic Journal of Working Life Studies, 2020)
The purpose of this article is to apply the method of the genre of studying chains of references to an instance of a secondary source of the contested concept of ‘resistance to change’ back to the primary source and thereby exercise criticism of the sources. This includes discussing whether the theory itself is empirically sustainable or sufficiently scientifically grounded. In the article, we adopt a theoretical lens of Critical Realist Discourse Analysis, mainly because it is sensitive to the importance of the influence of nondiscursive social positions on discourses. The primary source of the chain of theories of resistance to change turns out to be Kübler-Ross’s model of stages of dying patients’ reactions to their immanent death. We find that the model is systematically misinterpreted to fit the empirically false idea of resistance to change of the ideological discourses of management research.